A criação da doutrina de guerra contrarrevolucionária brasileira : a recepção do modelo francês dentro da revista A Defesa Nacional (1957-1965) - Santos, Jaderson Souza dos (2022)
In the present research, the reception, interpretation, analysis and reinterpretation of the French Doctrine of Counterrevolutionary Warfare by the magazine A Defesa Nacional between 1957 and 1965 was analyzed. Given the importance of the Magazine for the intelligentsia of the Brazilian military officer, the elaborations built on its pages allowed the dissemination of methods to combat revolutionary movements that were breaking out at that moment all over the world. Three distinct moments of the relationship between the Brazilian military and the French doctrine were observed: the first, an almost literal reception, where the recommendations of the French theorists were received as incorrigible. The second, when in an interpretation of the warfare techniques there are disagreements and gaps between the two understandings. The third moment contemplates the part where Brazilian officers start to demand the creation of their own and independent doctrine, which contemplates the national reality and its peculiarities. This claim brought with it a series of articles that started a theorization of the Counterrevolution, however, it was interrupted by time. From the year 1965 onwards, theorizations on the subject decrease significantly, interrupting the creation of a doctrine specific to the Brazilian armed forces.